The effect of make-a-match learning assisted by animation media on students’ higher-order thinking skills of human respiratory system material - Syahriani, Alica; Hasruddin, Hasruddin (Inornatus: Biology Education Journal, 2024)
This research aims to determine the effect of the make-a-match learning model assisted by animation media on students' high-level thinking abilities on the human respiratory system material. This research was conducted from October 2023 to June 2024 at SMAN 18 Medan using a quasi-experimental method with a two group pretest-posttest design. The sampling technique uses cluster random sampling. The experimental class XI MIA2 has 35 students and the control class XI MIA3 has 36 students. The research instrument used was the HOTs test in the form of multiple choices. The results showed that the average score for the experimental class was 82.40, while the average score for the control class was 69.33. Students who were taught using the make-a-match model assisted by animation media had higher average scores compared to students who were taught using the direct instruction learning model. Hypothesis testing with t-test statistics shows a significance value (2-tailed) of 0.000 < 0.05. This shows that the make-a-match learning model assisted by animation media has a significant effect on students' HOTs in the human respiratory system material at SMAN 18 Medan.